Nutrition Education for Preventing Stunting in Elementary Schools: A Systematic Review - Syihab, Syifa; Kumalasari, Isti (Prodi PGSD Penjas FPOK UPI, 2020)
Stunting has become a major problem in developing countries. The government has formulated various strategies to decrease the stunting prevalence in Indonesia. However, the number of programs to be implemented on the school aged children is scarce. Stunting in the school age can affect the productivity, motor development, and vulnerability from communicable diseases. The purpose of this study was to identify journals related to the nutrition education in preventing stunting in elementary schools. The study was a systematic review about nutrition education to prevent stunting in elementary school. There were 5 articles analyzed from the result of Google Scholar search, published from 2018 to 2020. The review focused on the type of intervention, goal, and effectiveness of the intervention. The result of the study showed that nutrition education could improve a short term knowledge. However, it had not been able to change the behavior and practice of healthy dietary habit. Nutrition education given to the teachers could improve their skills in assessing student nutritional status, thus an early detection can be administered well. A more comprehensive intervention, besides nutrition education, in preventing stunting in elementary school is needed.